The : Impact of Psychoanalytical Theory in the Character of Mrs. Ramsay in Virginia Woolf’s Novel ’To the Lighthouse ’ - Rashesd, Gulnaz (Journal of Peace, Development and Communication, 2023)
This article is written keeping in mind with the novel ‘To the Lighthouse’ written by Virginia Woolf. She is the modern novelist of the twentieth century. She wrote, ‘To the Lighthouse’ in 1927, which uses rudiments taken for Virginia’s own life. This novel contains deeper exploration of the human mind. Virginia Woolf sets this novel in the ‘Isle of Skye’ in Scotland. The main purpose of this article is to see the novel of Virginia Woolf with the lens of Sigmund Freud’s theory ‘Psychoanalysis’. This theory which deals with the unconscious mind of human. This article is dig out that how human behaviours and cognition effect the personality of persons which are settled in the mind of human. Virginia drifts the characters mind’s inner emotions especially the protagonist Mrs Ramsay who has the central figure of the story. By analysing of the theory of Psychoanalysis, the character of Mrs. Ramsay is explored in this article.